2018
DOI: 10.1590/s1677-5538.ibju.2016.0119
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of urethral duplication presenting with chronic bladder retention, left scrotal transposition and left renal agenesis

Abstract: Introduction and objectiveUrethral duplication is a rare congenital anomaly, with roughly 200 cases reported in the literature (1). It is more frequent in males, with few cases reported in females. The clinical presentation differs according to the anatomical variant present. The duplication most commonly occurs in the sagittal plane with one urethra located ventrally and the other dorsally (2). Usually the ventral urethra is the more functional of both. Duplications occurring in the coronal plane are quite ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Absence of single kidney and duplex kidney can also be observed through CT scans. Studies have shown that the clarity of CT has a certain impact on their diagnostic accuracy [ 29 ]. This is consistent with the results of this study that the accuracy of CT diagnosis of dysplasia of single kidney, absence of single kidney, horseshoe kidney, and duplex kidney would be improved with the clarity of CT image display.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of single kidney and duplex kidney can also be observed through CT scans. Studies have shown that the clarity of CT has a certain impact on their diagnostic accuracy [ 29 ]. This is consistent with the results of this study that the accuracy of CT diagnosis of dysplasia of single kidney, absence of single kidney, horseshoe kidney, and duplex kidney would be improved with the clarity of CT image display.…”
Section: Discussionmentioning
confidence: 99%
“…They initially performed a Mitrofanoff procedure to allow clear intermittent catheterization (CIC) to treat chronic urine retention. 20 Acimi et al 21 injected sclerosing agent into the accessory urethra, a procedure associated with a risk of injury to and fibrosis of the corpora cavernosa. Injecting sclerosing substance into the accessory urethra may damage the corporal bodies of the penis.…”
Section: Dovepressmentioning
confidence: 99%